Zinc and zinc transporters in macrophages and their roles in efferocytosis in COPD. - Rhys Hamon; Claire C Homan; Hai B Tran; Violet R Mukaro; Susan E Lester; Eugene Roscioli; Mariea D Bosco; Chiara M Murgia; Margaret Leigh Ackland; Hubertus P Jersmann; Carol Lang; Peter D Zalewski; et al. (PLoS ONE, 2014)
Our previous studies have shown that nutritional zinc restriction exacerbates airway inflammation accompanied by an increase in caspase-3 activation and an accumulation of apoptotic epithelial cells in the bronchioles of the mice. Normally, apoptotic cells are rapidly cleared by macrophage efferocytosis, limiting any secondary necrosis and inflammation. We therefore hypothesized that zinc deficiency is not only pro-apoptotic but also impairs macrophage efferocytosis. Impaired efferocytic clearance of apoptotic epithelial cells by alveolar macrophages occurs in chronic obstructive pulmonary disease (COPD), cigarette-smoking and other lung inflammatory diseases. We now show that zinc is a factor in impaired macrophage efferocytosis in COPD. Concentrations of zinc were significantly reduced in the supernatant of bronchoalveolar lavage fluid of patients with COPD who were current smokers, compared to healthy controls, smokers or COPD patients not actively smoking. Lavage zinc was positively correlated with AM efferocytosis and there was decreased efferocytosis in macrophages depleted of Zn in vitro by treatment with the membrane-permeable zinc chelator TPEN. Organ and cell Zn homeostasis are mediated by two families of membrane ZIP and ZnT proteins. Macrophages of mice null for ZIP1 had significantly lower intracellular zinc and efferocytosis capability, suggesting ZIP1 may play an important role. We investigated further using the human THP-1 derived macrophage cell line, with and without zinc chelation by TPEN to mimic zinc deficiency. There was no change in ZIP1 mRNA levels by TPEN but a significant 3-fold increase in expression of another influx transporter ZIP2, consistent with a role for ZIP2 in maintaining macrophage Zn levels. Both ZIP1 and ZIP2 proteins were localized to the plasma membrane and cytoplasm in normal human lung alveolar macrophages. We propose that zinc homeostasis in macrophages involves the coordinated action of ZIP1 and ZIP2 transporters responding differently to zinc deficiency signals and that these play important roles in macrophage efferocytosis.